(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Workplace deviances have always been critical issues in organization among researchers and managers. The occurrence of deviant behavior involves deception, employees thievery (stealing & shoplifting), squashing, unexcused absences, taking long breaks, rude violent behavior, and sexual abuses at the workplace accounts a big task for organizations. The impact of these behaviors is enormous on organization and individual & such behavior incur massive economic loss. To make organization productive & effective, we need to work hard to get over with this problem and bring harmony among them and in the organization. Keeping in mind the present study aims to study workplace deviant behavior in private sector among the working professionals. A sample of 60 working professional were taken from private sector undertaking and tested on the two aspects of workplace deviances ie., interpersonal deviances and organizational deviances. The aim of this paper is to study the impact of age and gender on workplace deviances. The age & gender has shown significant relation with interpersonal deviances than organizational deviances.